Comparative distribution and diversity of bats from selected localities in Sarawak - Kumaran, Jayaraj Vijaya; Ketol, Besar; Marni, Wahap; Sait, I.; Mortada, Mohd Jalani; Anwarali, F. A.; Fong, Pooi Har; Hall, L.S.; Abdullah, M.T (UNIMAS Publisher, 2011)
Surveys on the chiropteran diversity were conducted at eight different localities in Sarawak to document the bat diversity as well as to estimate the composition of bats in these areas. The major finding of bat surveys shows that montane areas have distinct chiropteran composition compared with those in lowland and logged areas. Disturbed habitats do pose a threat to the overall diversity of bats, with the generalist bats been more successful in colonising altered area than those with specialised habitat requirements. Sampling of bats targeted at different site and vegetation type from several protected areas in Sarawak have revealed the current record of bats in Sarawak and its diversity can be monitored for better management of biodiversity in this important region.